Investigating ‘Xindi Piano Teaching Method’ for music education in schools - Ye, Lanqing; Liu, Yaoping; Siripala, Wannaporn; Laknapichonchat, Tassanee; Arifani, Yudhi (Journal of Education and Learning (EduLearn), 2026)
This study examines the “Xindi Applied Piano Pedagogy” and its effects on the career growth of music teachers at the elementary and secondary school levels. It highlights the need to further study the integration of culture into music teaching through technology-enabled instructional design. The research is conducted with 12 students from three participating schools selected for the “Xindi Applied Piano Pedagogy” program through in-depth interviews. It is grounded in theory with a three-level coding system. The study suggests a three-step model for training music teachers: first, establishing a comprehensive educational framework; second, increasing subject scope and implementing concentrated instructional strategies; and third, evaluating students in a meaningful way that necessitates systematic changes to the curriculum. The study points out the synergistic interaction between higher educational institutions, elementary schools, and research institutions in “Xindi Applied Piano Pedagogy” that form a unified process of teacher training. It applies the deschooling theory in the pedagogy to encourage creative development as “Xindi Applied Piano Pedagogy” illustrates. This model brings together universities, research centers, and industries to create inventive ecosystems and utilizes plan, do, check, act (PDCA) cycles for continuous quality improvement. Further analysis of this approach in classroom settings is recommended by the study.